2012
DOI: 10.5455/msm.2012.24.94-99
|View full text |Cite
|
Sign up to set email alerts
|

Admission Rate of Patients with Most Common Psychiatric Disorders in Relation to Seasons and Climatic Factors During 2010/2011

Abstract: Introduction:Climate and its impact on human health and mental illness have been in the focus of the research since years in the field.Aim:The aim of the research is to study the admissions rate to the psychiatric clinic in correlation to seasons and climate.Material and method:The research was conducted in a Psychiatric clinic of the Clinical Center in Sarajevo. Randomly selected subjects (aged 5-89 years, 1316 males and 1039 females) N=2355, were interviewed by the Structural Clinical Interview (SCID) which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 11 publications
4
10
0
Order By: Relevance
“…The effect of seasonality in the hospital admission rate and LoS has been reported by many studies. [28][29][30][31][32] In our study, there were more admissions during month of March(10.2%) as compared to other months. The length of stay was maximum(21.8 days) in May and minimum(17.7 days) in March and there was significant association of LoS with month of admission.…”
Section: Discussionmentioning
confidence: 43%
“…The effect of seasonality in the hospital admission rate and LoS has been reported by many studies. [28][29][30][31][32] In our study, there were more admissions during month of March(10.2%) as compared to other months. The length of stay was maximum(21.8 days) in May and minimum(17.7 days) in March and there was significant association of LoS with month of admission.…”
Section: Discussionmentioning
confidence: 43%
“…In our study, deaths attributable to mental and behavioral disorders had the strongest seasonal pattern (37.4% increase in winter), but this grouping contributed only 0.8% of total winter mortality. Previous studies on seasonality of bipolar disorder and depressive disorder showed a clear peak in the winter months [ 29 , 30 , 31 ]. A longitudinal study conducted in Ireland reported the highest levels of depressive symptoms in winter, and those who live in areas with longer daily hours of sunshine experienced lower occurrence rate of depressive symptoms [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…As to this question has not yet is given a definitive answer, it is hoped that further research, which would take all this into account will give clear answers regarding complex phenomenon of comorbidity of psychiatric disorders (14, 15, 16). …”
Section: Discussionmentioning
confidence: 99%